qanda-logo
search-icon
Symbol

Calculator search results

Solve the equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Graph
$y = 6 + x$
$y = 3 x$
$x$Intercept
$\left ( - 6 , 0 \right )$
$y$Intercept
$\left ( 0 , 6 \right )$
$x$Intercept
$\left ( 0 , 0 \right )$
$y$Intercept
$\left ( 0 , 0 \right )$
$x = 3$
$ $ Solve a solution to $ x$
$\color{#FF6800}{ 6 } \color{#FF6800}{ + } \color{#FF6800}{ x } = 3 x$
$ $ Organize the expression $ $
$\color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 6 } = 3 x$
$x + 6 = \color{#FF6800}{ 3 } \color{#FF6800}{ x }$
$ $ Move the variable to the left-hand side and change the symbol $ $
$x + 6 \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 0$
$x \color{#FF6800}{ + } \color{#FF6800}{ 6 } - 3 x = 0$
$ $ Move the constant to the right side and change the sign $ $
$x - 3 x = \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = - 6$
$ $ Organize the expression $ $
$\color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = - 6$
$\color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
$ $ Change the sign of both sides of the equation $ $
$2 x = 6$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ 6 }$
$ $ Divide both sides by the same number $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ 3 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
check-iconSearch by problem image
check-iconAsk 1:1 question to TOP class teachers
check-iconAI recommend problems and video lecture